2014
DOI: 10.1097/fpc.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance in ABCB1 and CYP3A5 does not contribute toward the development of chronic kidney disease after liver transplantation

Abstract: An individual's risk of developing CKD after LT is not associated with genetic variation in either recipient or donor CYP3A5 or ABCB1 genotype status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[23] Several studies show a prevalence of > 50% of the LT recipients with a CKD defined as an eGFR of <60 mL/min/1.73 m 2 . [7,8] Our ITT and PP analysis showed lower rates with a prevalence of 30% to 50% of the LT recipients having an eGFR of <60 mL/min/1.73 m 2 . This difference could be explained by the height of the TAC trough levels.…”
Section: Discussionmentioning
confidence: 81%
“…[23] Several studies show a prevalence of > 50% of the LT recipients with a CKD defined as an eGFR of <60 mL/min/1.73 m 2 . [7,8] Our ITT and PP analysis showed lower rates with a prevalence of 30% to 50% of the LT recipients having an eGFR of <60 mL/min/1.73 m 2 . This difference could be explained by the height of the TAC trough levels.…”
Section: Discussionmentioning
confidence: 81%
“…Evaluation of parameters related to selection showed that in all of the studies, sample population was representative of the community and both genotype groups were selected from the same population except one in which patients with developed acute cellular rejection were selected, eleven studies did not obtain blood samples at the same time for all participants and that was one of the reasons for their exclusion from the analyses, seven studies did not begin their experiments from first post‐transplant day, when tacrolimus was administered for the first time . Two parameters were checked as confounders, and apart from five studies, others did not assess one or both of them.…”
Section: Resultsmentioning
confidence: 99%
“…Two parameters were checked as confounders, and apart from five studies, others did not assess one or both of them. Appraisal of outcomes revealed that in 23 studies, outcomes of interest were not presented (eg, because of nonsignificant data) or presented improperly (eg, as median) which led to the exclusion of the study from the analyses or obligated us to estimate required data . Eight studies did not continue blood level measurement at specified time points for at least one month or did not mention the time of measurement clearly .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respect to CYP3A5, Fukudo et al [165] did not find a significant association in donors, although they only used changes in serum creatinine concentrations (and not creatinine clearance) for diagnosing chronic nephrotoxicity. Tapirdamaz et al [166] reported that neither the CYP3A5 6989A>G nor ABCB1 3435C>T genotype of either donor or recipient was associated with risk of chronic kidney disease, but they did not consider as exclusion criteria other different causes of chronic kidney disease, so further studies are needed.…”
Section: Impact Of Pharmacogenetics On Clinical Outcomesmentioning
confidence: 99%